MOBILIZATION OF TRANS-CINNAMIC ACID, PRECURSOR OF LIGNINS IN DATE PALM ROOTS OVER A COMPATIBLE INTERACTION WITH THE PATHOGENIC AGENT OF BAYOUD DISEASE, FUSARIUM OXYSPORUM F. SP. ALBEDINIS - Boucenna-Mouzali, B; Gaceb-Terrak, R; Azouaoui-Ait Kettout, T; Touam, D; Rahmania, F (university of el oued/جامعة الوادي, 2021)
Bayoud disease of date palm Phoenix dactylifera L. is the result of specific interactions established between this plant and Fusarium oxysporum f. sp. albedinis (F.o.a.). Facing this aggression, the host plant uses its constitutive preventive system and also defense mechanisms triggered by the pathogen. Our work is based on the identification of secondary metabolites produced during this confrontation in date palm roots. Our results show that during infection, susceptible cultivar accumulates considerable proportions of para-hydroxybenzoic acid. In soils infested by F.o.a., a significant decrease of para-hydroxybenzoic acid and an accumulation of para-hydroxycinnamic acid were observed in the roots of resistant cultivar. The analysis we realized shows that preferential orientation of the precursor “trans-cinnamic acid” of phenolic metabolism is activated in the root in contact with the causative agent of Bayoud. It also shows the presence of a greatest amount of lignin in resistant cultivar roots when compared with the susceptible ones.
Article
Keywords: date palm roots; bayoud desease; host-pathogen interaction; phenolic acids; lignin